Analisis Waktu Kunjungan Pasien Kronis di Depo Farmasi Rawat Jalan RSUD dr. Hardjono S. Ponorogo dalam Sistem Layanan BPJS Kesehatan - Ita Octafia; Luvia Hardiana; Susilowati Andari; Riza Mazidu Sholihin; Iffah Qurratu Aini (Jurnal Sosial Teknologi, 2026)
Chronic diseases are a major cause of morbidity and mortality in Indonesia. To ensure patients receive optimal therapy, BPJS Kesehatan (Indonesian Health Insurance) has established a regular patient visit schedule through the Referral Back Program (PRB). However, discrepancies often occur between patient visit times. To control medication administration, Dr. Harjono S Ponorogo Regional General Hospital (RSUD) formed a verification team. The purpose of this study was to analyze the visit times of chronic patients at the outpatient pharmacy depot of Dr. Harjono S Ponorogo Regional General Hospital within the BPJS Kesehatan service system. This study used a cross-sectional design. The research instrument was an observation sheet to record the number of prescriptions for chronic patients that were inconsistencies with the visit schedule from October to December 2024. Data analysis is the calculation of the number of chronic prescriptions against the visit schedule. Based on research at RSUD dr. Hardjono S. Ponorogo in October 2024 there was a rejection of 1.13%, in November 2024 there was a rejection of 0.93% and in December 2024 there was a rejection of 1.28%. Influencing factors are patient condition, compliance with treatment and external factors. Based on the results of research on the Analysis of Chronic Patient Visit Time at the Outpatient Pharmacy Depot RSUD dr. Harjono S. Ponorogo in the BPJS Health Service System, rejections still occur in the BPJS Health application system.